The Role of Product and Process Innovation in CGE Models of Environmental Policy - Claudio Baccianti; Andreas Löschel (WWWforEurope, 2014)
In the last two decades, large scale CGE models used for environmental policy assessment underwent an important upgrade to integrate endogenous technological progress. Nevertheless, several complexities of innovation are still neglected even if they are of primary interest for policymakers. This paper provides a review of the current state of the art in the CGE modelling literature through a special lens. We discuss how existing models deal with different types of innovation (i.e. product and process innovation) and how differences in innovation activities influence modelling results. We also emphasise the implications of product innovation in a multisector framework, which has received little attention in the literature.
Keywords: O41; O40; O47; 330; CGE models; ecological innovation; economic growth path; green jobs; innovation; innovation policy; social innovation; socio-ecological transition; sustainable growth